Molecular modelling studies of DNA damage recognition - Jiranusornkul, Supat (2008)
How DNA repair proteins search and recognise the rare sites of damage from the massive numbers of normal DNA remains poorly understood. FapydG (2,6-diamino-4-hydroxy-5-formamidopyrimidine) is one of the most prevalent guanine derived lesions involving opening of the imidazole ring. It is typically repaired by formamidopyrimidine-DNA glycosylase (Fpg) as an initial step in base excision repair; if not repaired, the lesion generates a G: C -+ T: A transversion. Unfortunately, studies on the recognition of FapydG have been hindered by difficulties to synthesise and incorporate the FapydG residue into a DNA duplex. Crystal structures of Fpg-DNA complexes have demonstrated three common recognition events: the protein specifically binding to the extrahelical lesion, bending DNA centred on the damaged base, and flipping the damage into the pocket. Thus, molecular modelling and dynamics simulation have been used to gather dynamical information of those recognition events for damaged and undamaged DNA. The simulations were initially performed when FapydG or G occurs in several dodecamer B-DNA sequences in aqueous solution, then inside the lesion-recognition pocket of Fpg, and during the flipping pathway from the helical stack to an extrahelical position. The influence of the damage on DNA stability and flexibility was first investigated. Energetic analysis revealed that damage to DNA does appear to destabilise the duplex. DNA curvature analysis and a novel combined method of the principal component analysis (PCA) and the Mahalanobis distance (DM) indicated that damaged DNA can adopt the observed protein-bound conformation with lower energetic penalties than its normal counterpart. Results of these studies have provided the validation of DNA bending enhancement by the FapydG lesion. It also suggested that intrinsic DNA bending could be a principal element of how the repair protein locates the lesion from vast expanse of normal bases. Considering the specific recognition of FapydG by Fpg, the aF-/39 loop of the Fpg enzyme may function as a gatekeeping to accommodate the lesion while denying the normal base. Remarkably fluctuating movement of the flipped G residue and the aF-ß9 loop is due to the formation of the non-specific Fpg/G complex with a lower binding energy by 8.4 kcal/mol compared to the specific Fpg/FapydG complex. Free-energy profiles for both damaged and undamaged base flipping were generated from the umbrella sampling simulations and the Weight Histogram Analysis Method (WHAM). An energy barrier for flipping the damage out from the helix is 2.7 kcal/mol higher than its equivalent G and the lesion is highly stabilised inside the pocket. In contrast, G flipping seems to be rapidly rotated out and into the duplex without the formation of a specific complex. These studies could unravel a potentially comprehensive process of the repair protein to find and recognise the lesion through the slow kinetic pathway in which the more deformable damaged DNA is initially located by the protein; the protein subsequently compresses the duplex into an appropriate angle and direction to form a specific protein-DNA complex prior to being flipped and repaired.